A profissionalização em ciências ambientais no Brasil : formação, associação e regulamentação - Santo, Najó Glória dos (2019)
The Thesis analyzes the historical course of the professionalization in environmental sciences in Brazil, taking as Ariadne thread the geography of the academic formation, the influences of the association in the organization of professional collectives and the legal ways that regulate the profession of the environmental manager in the Brazilian territory. Initially, it presents the theoretical itinerary of the categories of work, profession and professionalization. The object of this research was delimited by the offer of undergraduate education (Technology and / or Bachelor degree courses), and stricto sensu postgraduate (Academic and Professional Master and Doctorate) which have environmental denomination in their nomenclature and are offered by public and private higher education institutions. The objective of the research was to characterize the contradictions between environmental issues and the needs of environmental manager training in the political, economic, institutional, geographical and professional dimensions. This study has a descriptive-exploratory nature. The research approach was historical-critical based on the dialectical method. Documentary research was the main instrument for collecting and analyzing information. The results indicate that the uncertainty of the regulation of the environmental manager profession signals a political aspect, subjected to market demands to the detriment of environmental issues. Among other considerations, the following stand out: a) the exponential growth of vacancies in private institutions, which denotes the prevalence of economic interest; b) the dispersion of the courses offered by private institutions that reach the most remote places in the national territory. Therefore, The thesis confirms the urgency of adopting regulatory measures that prevent the market predatory advance on the environment.. It is concluded that the professionalization in environmental sciences adds economic and symbolic value based on the market matrices.